Analisis Kebijakan Pemajakan atas Tansaksi Perdagangan Aset Kripto di Indonesia - Yusuf Afani; Maria R.U.D. Tambunan (Magister Akuntansi Universitas Pancasila, 2022)
ABSTRACT The number of investors in crypto assets is increasing, exceeding the number of investors in the capital market, mutual funds, and state securities. The increase in the number of investors is also in line with the tremendous rise in the value of crypto asset transactions in recent years. That significance encourages the Indonesian government to tax crypto asset trading transactions. However, the taxation of crypto asset transactions raises concerns about the disruption of Indonesia's crypto asset innovation climate. This study describes crypto asset policy in Indonesia and analyzes them based on compliance with taxation principles. The method used is qualitative. While data collection using literature study. Tax with a special mechanism is imposed on the trading transaction of the crypto asset and mining, while tax with the general mechanism is imposed on the exchanger/e-wallet fee. The imposition of value-added tax is analyzed based on fulfilling the principles of income productivity, certainty, convenience, simplicity, and neutrality. The imposition of income tax is examined with these principles, plus the principle of equity. The imposition of value-added tax on the supply of crypto assets fulfills the principles of income productivity, certainty, convenience, simplicity, and neutrality, likewise with the imposition of income tax. However, the principle of equity is not fulfilled by the imposition of income tax because the goal of this policy is ease of administration, primarily simplicity. ABSTRAK Jumlah investor aset kripto semakin meningkat, melampaui jumlah investor pada pasar modal, reksa dana, dan surat berharga negara. Peningkatan jumlah investor juga sejalan dengan meningkatnya nilai transaksi aset kripto yang fantastis beberapa tahun belakangan. Hal tersebut mendorong pemerintah Indonesia untuk memajaki transaksi perdagangan aset kripto. Akan tetapi pemajakan transaksi aset kripto ini menimbulkan kekhawatiran akan terganggunya iklim inovasi aset kripto di Indonesia. Penelitian ini bertujuan memberikan gambaran kebijakan aset kripto di Indonesia dan menganalisisnya berdasarkan pemenuhan asas-asas pemajakan. Metode yang digunakan adalah kualitatif. Sedangkan pengumpulan data menggunakan studi literatur. Transaksi pedagangan aset kripto dan mining dikenakan pajak dengan mekanisme khusus, sementara jasa exchanger/e-wallet dikenakan pajak dengan mekanisme umum. Pengenaan pajak pertambahan nilai dianalisis berdasarkan pemenuhan asas produktivitas pendapatan, kepastian, kenyamanan, kesederhanaan dan netralitas. Sedangkan pengenaan pajak penghasilan dianalisis dengan asas-asas tersebut ditambah dengan asas keadilan. Pengenaan pajak pertambahan nilai atas penyerahan atas aset kripto memenuhi asas produktivitas pendapatan, kepastian, kenyamanan, kesederhanaan, dan netralitas. Begitu pula dengan pengenaan pajak penghasilan. Akan tetapi, asas keadilan tidak terpenuhi dalam pengenaan pajak penghasilan karena tujuan utama dari kebijakan pemajakan ini adalah kemudahan administrasi terutama kesederhanaan